Relation between motor competence and academic achievement: The mediating role of fitness and cognition in boys and girls - Antonio Fernández-Sánchez; Abel Ruiz-Hermosa; Andrés Redondo-Tébar; Ana Díez-Fernández; Vicente Martínez-Vizcaíno; María Eugenia Visier-Alfonso; Mairena Sánchez-López (PLoS ONE, 2025)
Introduction Gross motor competence is positively associated with academic achievement in schoolchildren, potentially mediated by fitness and cognition. However, the extent to which these mediators contribute—and whether effects differ by sex—remains unclear. This study explored the mediating roles of specific fitness components and executive function in the relationship between gross motor competence and academic achievement, considering sex differences. Methods This cross-sectional study included 562 Spanish schoolchildren aged 9–11 years (293 girls). Gross motor competence was evaluated using the Movement Assessment Battery for Children-Second Edition; fitness components (cardiorespiratory fitness, speed/agility, upper and lower body strength) through the ALPHA-Fitness test battery; executive function using the NIH Toolbox Battery; and academic achievement from school grades in language and mathematics. Serial multiple mediation models were applied using the PROCESS macro in SPSS, adjusted for age, BMI, and maternal education level. Analyses were conducted for the total sample and by sex. Results Both fitness and executive function partially mediated the relationship between gross motor competence and academic achievement. In the total sample, direct effects explained most of the association (51–73%), followed by the cognitive pathway (20–31%), fitness pathway (11–19%), and multiple pathway—gross motor competence, fitness, executive function, and academic achievement—(4–9%). Sex-specific analyses showed that cognitive mediation was predominant in boys, accounting for over half of the total effect (56–69%), with no direct effect observed. In contrast, fitness mediation was more relevant in girls, especially through cardiorespiratory fitness and speed/agility, each contributing up to 20% of the effect. The multiple pathway was also significant in girls. Conclusions Enhancing motor competence may improve academic outcomes, partly through gains in fitness and executive function. These findings support implementing integrated school programs, tailored to sex-specific needs—emphasizing cognitively engaging activities for boys and fitness-focused strategies for girls. The cross-sectional design implies association, not causality.